Women in Gendered Fisheries: Roles, Issues and Challenges in Cambodia, Indonesia, Vietnam and Philippines - Villarosa-Tanchuling, Ma. Linnea (Jurnal Perempuan, 2017)
This paper is a synthesis of the results of the case studies on women’s situation in fisheries done by the members of the SEA Fish for Justice Network. The network is composed of 15 non-government and fishers organizations from the Southeast Asia region. It envisions equity in access to and control over off-shore, coastal and inland aquatic natural resources including the termination of suffering caused by unsustainable resources and/or privatized control over communal resources. The case studies were conducted by SEAFish Network members in Cambodia, Indonesia, Vietnam and Philippines in the second and third quarter of 2008 to highlight the roles, issues and challenges faced by women in coastal communities as well as the spaces provided them to facilitate their empowerment. The network members who conducted the studies were FACT (Cambodia), KIARA (Indonesia), MCD (Vietnam) and PROCESS-Bohol, CERD, and Tambuyog Development Center (CERD).